Darwin studies - Hodge, M. J. S. (Michael Jonathan Sessions), 1940- author.
1 online resource (356 pages).
Keywords: This is the second of a pair of volumes by Jonathan Hodge, collecting all his most innovative, revisionist and influential papers on Charles Darwin and on the longer run of theories about origins and species from ancient times to the present. The focus here is on Darwin himself and the development of his theories. Darwin is now such an iconic hero in our histories and such a commanding authority in our sciences that it has become a serious challenge to study him as just another disaffected medical student - or would-be vicar, aspiring zoology professor or gentleman of independent means -- thinking about sexual reproduction in animals and plants, about coral islands or about rock strata and fossils in post-Napoleonic Edinburgh, Cambridge, South America and London. But the challenge is one well worth taking up, as the papers here demonstrate, for such studies require us integrate the precise details of his inquiries with those larger scientific, metaphysical, religious and political issues of the day that a young, ambitious 'philosopher' and 'naturalist' was then expected to engage. This contextual understanding can then allow us to reinterpret his relations to such longer- run legacies as Christian Platonism, Enlightenment materialism and British capitalism. Together with the companion volume devoted to those and other long run legacies, this volume offers throughout reinterpretations of both the theorist and his theories.